PROSES KOMUNIKASI DIALOGIS PELITA DESA NURSERY DALAM MEMBERDAYAKAN PETANI MITRA TANAMAN HIAS DI KOTA BOGOR - Fitri, Anisa Nurul; Yusnita, Titien; Ernawati, Erna (Fakultas Ilmu Dakwah dan Komunikasi, 2023)
This research aims to determine dialogical communication in empowering Pelita Desa Nursery partner farmers in Bogor City. The research method uses qualitative. This research involved informants from partner farmers and Pelita Village Nursery staff. The results of this research are that the communication strategy carried out by Pelita Desa Nursery is a dialogical communication strategy which involves an open and responsive exchange of ideas and opinions. This can be seen from the involvement of communicators and communicants in listening to each other carefully, responding with empathy, and building mutually beneficial discussions between Pelita Desa Nursery and partner farmers so that two-way communication can occur which creates a reciprocal process between communicators. with communication built on 1) openness, 2) empathy, 3) supportive attitude, 4) positive attitude, 5) equality.